Active Anaerobic Archaeal Methanotrophs in Recently Emerged Cold Seeps of Northern South China Sea - Zhang, Tingting; Xiao, Xi; Chen, Songze; Zhao, Jing; Chen, Zongheng; Feng, Junxi; Liang, Qianyong; Phelps, Tommy J.; Zhang, Chuanlun (Frontiers in Microbiology, 2020)
Cold seep ecosystems are developed from methane-rich fluids in organic rich continental slopes, which are the source of various dense microbial and faunal populations. Extensive studies have been conducted on microbial populations in this unique environment; most of them were based on DNA, which could not resolve the activity of extant organisms. In this study, RNA and DNA analyses were performed to evaluate the active archaeal and bacterial communities and their network correlations, particularly those participating in the methane cycle at three newly developed cold seeps in the northern South China Sea (nSCS). The results showed that both archaeal and bacterial communities were significantly different at the RNA and DNA levels, revealing a high abundance of methane-metabolizing archaea and sulfate-reducing bacteria in RNA sequencing libraries. Site ROV07-01, which exhibited extensive accumulation of deceased Calyptogena clam shells, was highly developed, and showed diverse and active anaerobic archaeal methanotrophs (ANME)-2a/b and sulfate-reducing bacteria from RNA libraries. Site ROV07-02, located near carbonate crusts with few clam shell debris, appeared to be poorly developed, less anaerobic and less active. Site ROV05-02, colonized by living Calyptogena clams, could likely be intermediary between ROV07-01 and ROV07-02, showing abundant ANME-2dΙ and sulfate-reducing bacteria in RNA libraries. The high-proportions of ANME-2dΙ, with respect to ANME-2dⅡ in the site ROV07-01 was the first report from nSCS, which could be associated with recently developed cold seeps. Both ANME-2dΙ and ANME-2a/b showed close networked relationships with sulfate-reducing bacteria; however, they were not associated with the same microbial operational taxonomic units (OTUs). Based on the geochemical gradients and the megafaunal settlements as well as the niche specificities and syntrophic relationships, ANMEs appeared to change in community structure with the evolution of cold seeps, which may be associated with the heterogeneity of their geochemical processes. This study enriched our understanding of more active sulfate-dependent anaerobic oxidation of methane (AOM) in poorly developed and active cold seep sediments by contrasting DNA- and RNA-derived community structure and activity indicators.